Bioactive compounds of cocoa beans, cocoa, and chocolate and their effects on cognitive function and possible use in cardiometabolic diseases prevention - Renata Gołdys; Karolina Bernacka; Iwona Urbanowicz; Izabela Fecka (Polish Pharmaceutical Society, 2023)
Cacao seed (Cacao semen) is a plant material known since ancient times and is widely used for food and pharmaceutical purposes. Cocoa seed products such as chocolate and chocolate confectionery are among the most widely consumed types of sweets. Growing health awareness among consumers has made dark chocolates and other products with a high cocoa content increasingly popular. Their health-promoting effects, resulting from habitual consumption, are determined by the content of cocoa pulp (mass), in which biologically active compounds are found. Numerous polyphenols, such as procyanidins, flavanols, and flavonols; methylxanthines, as well as amines, amides, etc., have been identified in cocoa beans and cocoa products. They show beneficial effects on the cardiovascular system, lowering the risk of cardiovascular incidents through antioxidant, anti-inflammatory, and vasodilatory effects, improving vascular endothelial function, lowering platelet activity and blood pressure, and regulating lipid metabolism. Moderate chocolate consumption is also associated with a lower risk of diabetes, as a result of increased tissue sensitivity to insulin, improved glycemia, and lipid profile. In recent years, the impact of chocolate and cocoa on mood, cognitive function, and episodic memory has been studied. A correlation between chocolate consumption and reduced mortality from Alzheimer's disease is also indicated. Due to the presence of methylxanthines and mood-enhancing effects, chocolate is classified as a mood food. Currently, it is suggested that chocolate, previously associated with overweight and obesity, may have beneficial effects in regulating appetite, and regular consumption of dark chocolate in moderate amounts is associated with reduced body weight and BMI. The above-mentioned health-promoting properties of the cocoa seeds, cocoa, and chocolate constituents could potentially be applied in the prevention and in supporting the treatment of patients with cardiometabolic diseases and cognitive dysfunction.